I-Con / Nasrul Nasruddin ... [et al.] - Nasruddin, Nasrul; Noor 'Adzam, Muhammad Nur Akmal; Zainudin, Muhammad Amirul; Hamzah, Amirul Aqlan; Hamide, Akmal Hanif (2018)
The objectives in creating this product is to help people to gain water for themselves when its flood season, to help people have water when they are camping and to provide fresh water for people at the shelter when there are no clean water. This product itself is a novelty to the society as they never seen something like it in Malaysia being commercialize. Hence, every parts of this product is something new although it applies simple condensation process. The special criteria of this product are it is light in mass as it only weight 2kg, small in size which is 0.2m x 0.2m x 0.3m and it is portable because it can be use anywhere and anytime. This product will provide lots of people clean water anytime they want. Hence, this product will be beneficial to the society. This product has a great potential to be commercialize in this country as there are no company ever created it there.